Converted battery-powered electric motorcycle and hydrogen fuel cell-powered electric motorcycle in South East Asia: development and performance test - Weigl, J. D. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents the development and performance test of electric motorcycle in South East Asia i.e. in Singapore and Malaysia. National University of Singapore (NUS) team converted ICE based motorcycle (Honda CBR400) into battery electric motorcycle using lead acid battery pack and lithium polymer battery pack. Fuel Cell Vehicle Group in Universiti Teknologi Malaysia (UTM) built a fuel cell electric motorcycle which used hydrogen fuel cell system (named H2Motive® fuel cell motorcycle), lithium polymer battery pack and ultra-capacitor module. Road tests have been conducted to test the performance of both electric motorcycle types. Performance of H2Motive® fuel cell motorcycle was done by participating South African Solar Challenge 2008 in technology class. Results showed that H2Motive® fuel cell motorcycle was able to travel about 2400 km. Some roads were at steep and hilly climb and the motorcycle could stand during heavy rain. The converted CBR400 was tested in World Advanced Vehicle Expedition with 1600 km travel distance. NUS team's e-bike claimed third spot in that rally. Both type of electric vehicle performed well during the rally. It can be concluded that two of them were ready for gaining road-legal status.